(untitled) (International Journal of Food and Nutritional Sciences, 2023)
greenhouse studies were embraced to evaluate the viability of chosen biocontrol specialists in blend with fungal disease against damping-off and shrink microbes of various crops. Pythiumsp and Fusariumsp were found in infected plants and soil samples to be the wilt pathogens that caused various plants crops to wilt. They were found to cause 50-85% seedling loss in plants crops in a pathogen city test carried out in a greenhouse. The biocontrol agents were tested for their ability to promote growth and prevent disease in a greenhouse setting. Seedling vigor, total biomass, disease incidence, and biocontrol efficiency were all higher when Azotobacter chroococcum, Bacillus megaterium, Pseudomonas fluorescens, Bacillus subtilis, and Trichoderma harzianum were utilized in combination.